Consumer behaviour - Sethna, Zubin (New Delhi Sage, 2023)
Consumer behavior is the study of how individuals and groups select, purchase, use, and dispose of goods, services, ideas, and experiences to satisfy their needs and wants. It is a multi-stage process influenced by psychological, personal, and social factors, such as emotions, culture, personal values, and marketing efforts. Understanding consumer behavior is crucial for businesses to develop effective marketing strategies.